Challenges facing psychiatric intensive care during COVID-19: mitigating the risk of transmission on a PICU. (1st September 2020) - Pugh, Ria; Skelton, Luke; Blake, Lucy; Butler, Margaret; Harries, Bethan; Sethi, Faisil
This is the second of five brief reports which document the experience of a London psychiatric intensive care unit (PICU) which faced an outbreak of COVID-19 infection relatively early in the pandemic. The aim is to share what was learnt and examine the challenges which lie ahead for psychiatric intensive care services. This article will present how the PICU adapted to the changing landscape with consideration of the COVID-19 infectious window, infection prevention and control protocols and the unique challenges faced by PICU services.